Inundation Risk Level Tsunami in Trenggalek District, Indonesia - Basid, Abdul; Mahardika, I Ketut; Subchan, Wachju; Astutik, Sri; Rusli, Rusli; Jannah, S.D.N.; Rozikan, Rozikan (Indonesian Journal on Geoscience, 2026)
The southern coast of Trenggalek District is prone to tsunami disasters, because it is located north of the megathrust zone. This study aims to map the level of tsunami inundation risk in The Trenggalek District, especially of the coast of Watulimo Subdistrict. This mapping was done with the help of Model Builder in ArcGIS software, using scenarios of tsunami wave heights on the shore of 1 m, 2 m, 5 m, 15 m, 27 m, and 30 m. The risk map of tsunami inundation was obtained by combining the tsunami hazard map with the vulnerability map. The study results show that the area of tsunami inundation at a high-altitude scenario with wave heights of 1 m has low, medium, and high-risk levels covering 0.254 km², 0.240 km², and 0.032 km², respectively. In the 27 m scenario, which is the worst-case scenario according to Meteorology, Climatology, and Geophysics Agency (BMKG), the areas of inundation at low, medium, and high-risk levels reach 23.032 km², 16.471 km², and 7.904 km², respectively. In this 27 m scenario, four villages in Watulimo Subdistrict are almost entirely inundated by the tsunami. The results of this study are expected to be used as the material for tsunami disaster mitigation in the Trenggalek District.